Effects of Earnings Forecasts and Heightened Professional Skepticism on the Outcomes of Client–Auditor Negotiation - Brown-Liburd, Helen L.; Cohen, Jeffrey; Trompeter, Greg (2013)
Ethics has been identified as an important factor that potentially affects auditors’ professional skepticism. For example, prior research finds that auditors who are more concerned with professional ethics exhibit greater professional skepticism. Further, the literature suggests that professional skepticism may lead the auditor to more vigilantly resist the client’s position in financial reporting disputes. These reporting disputes are generally resolved through negotiations between the auditor and client to arrive at the final reported amounts. To date, the role that professional skepticism potentially plays in the negotiation process has been relatively unexplored. The literature prior to the enactment of Sarbanes–Oxley (SOX) suggests that auditors are more likely to approve a client position when the matter in dispute is relatively ambiguous and when changing the client’s position will result in the client failing to meet analysts’ expectations. However, changes resulting from SOX have led auditors to be more vigilant and therefore results found in the pre-SOX environment may not hold in the current environment where auditors are held more accountable for their actions. Results from an experiment with experienced audit managers and partners suggest that in the post-SOX climate, auditors’ negotiations do not appear to be substantively influenced by management being able to meet or beat forecasts. Moreover, we find that when auditors exhibit heightened professional skepticism, they are more ethical by being conservative and they stand more resolute than when auditors do not exhibit heightened professional skepticism. Finally, although we do not find a main effect for the influence of earnings forecast, we do find a significant interaction between earnings forecast and heightened professional skepticism. Implications for practice and research are then presented.
Keywords: audit judgment; Auditor’s ethics; Earnings management; Negotiation; Professional skepticism